Age-Dependent Dispersal and Relatedness in Tiger Sharks (Galeocerdo cuvier) - McClain, Margaret A.; Hammerschlag, Neil; Gallagher, Austin J.; Drymon, J. Marcus; Grubbs, R. Dean; Guttridge, Tristan L.; Smukall, Matthew J.; Frazier, Bryan S.; Daly-Engel, Toby S. (Frontiers in Marine Science, 2022)
Understanding dispersal in large marine fauna is necessary for conservation, but movement patterns often vary widely by sex and life stage. In sharks, genetic studies have shown evidence of widespread male-biased dispersal, though tagging and tracking studies on the same populations show both sexes using site fidelity, including philopatry, and moving similar distances. We used a suite of microsatellite loci and DNA samples from 362 previously-tagged Tiger Sharks (Galeocerdo cuvier) in the northwestern Atlantic, including a large number of residential juveniles, to evaluate reproductive dispersal in light of demographic and published tracking data. We found that lumping size classes together resulted in genetic panmixia across sites, but systematic removal of large individuals showed significant population-level differentiation and three separate population clusters among juveniles >260 cm total length. Tests for relatedness found that 8.9% of our sample set was comprised of first-order related pairs (N = 16), including several full siblings from different litters, a sign of multi-cycle genetic monogamy which carries implications for effective population size. By mapping genetic assignments of juveniles, we identified a signature of fine-scale genetic structure suggesting broad biparental site fidelity to reproductive habitat in the northeast Gulf of Mexico, which is concordant with both genetic and tracking data. Taken together, these findings demonstrate how lumping individuals from different life stages in genetic studies may obscure fine-scale genetic structure, confounding future conservation efforts.